Principles of communications : Systems,Modulation and Noise - Ziemer,R.E (Jaico Pub, 2002)
Principles of communications : Systems,Modulation and Noise / Ziemer,R.E.. -- Kolkata: Jaico Pub., 2002 621.382 Z67e3 3rd ed No. of Copies : 1